Halogen-free flame-retardant cable and preparation method thereof
By using core-shell flame retardant in the cable, combining silica fibers and phosphate, the flame retardant performance of the cable is improved, the pollution problem during combustion of polyvinyl chloride materials is solved, and efficient flame retardant effect and isolation are achieved. Thermal performance.
Patent Information
- Application Number
- CN202411199894.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-08-29
AI Technical Summary
The polyvinyl chloride materials used in existing cables release corrosive gases when burned, pollute the environment, and the halogen-free flame retardant materials have low flame retardant properties, so their flame retardancy needs to be improved.
Co-extruded core-shell flame retardant and polyethylene as cable sheath material, silica fiber and phosphate as heat insulation filler, and sulfonate-based polystyrene microspheres and modified ceramic fibers are used to form core-shell flame retardant, enhances the flame retardant performance of cables.
It realizes the efficient flame retardant effect of the cable, interrupts combustion, promotes charcoal formation, improves the quality and continuity of the carbon layer, prevents secondary combustion, and optimizes the flame retardant and thermal insulation performance of the cable.
Smart Images

Figure BDA0005017579110000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cables, in particular to a halogen-free flame-retardant cable and a preparation method thereof. Background Art
[0002] As a supporting industry of the power industry, one of the pillar industries of the national economy, the wire and cable industry plays an extremely important role and position in the national economy.
[0003] Polyvinyl chloride is often used as insulation and sheath materials for control cables. However, polyvinyl chloride contains chlorine, which will increase smoke release and release corrosive gases when burned, polluting the environment. Therefore, halogen-free plastic or rubber materials need to be used as insulation and sheath materials. However, their flame retardancy is low and their flame retardancy needs to be improved. Summary of the invention
[0004] The object of the present invention is to provide a halogen-free flame-retardant cable and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a halogen-free flame-retardant cable, comprising a copper conductor, a polyethylene insulation layer, a copper braided shielding layer, and a flame-retardant layer, wherein the flame-retardant layer is composed of a core-shell flame retardant, a polyethylene resin, a lubricant, and an antioxidant.
[0006] Furthermore, the polyethylene resin is a mixture of linear low-density polyethylene, high-density polyethylene, and ethylene-vinyl acetate copolymer in a weight ratio of 40-50:10-20:20-35.
[0007] Furthermore, the density of the linear low-density polyethylene is 0.920 g / cm 3 , the melt index is 2.0g / 10min.
[0008] Furthermore, the density of the high-density polyethylene is 0.953 g / cm 3 , the melt index is 0.4g / 10min.
[0009] Furthermore, the lubricant is polyethylene wax or zinc stearate.
[0010] Furthermore, the antioxidant is dilauryl thiodipropionate or antioxidant 1010.
[0011] Furthermore, the preparation method of the core-shell flame retardant is:
[0012] (1) placing silica fiber in a reaction device with a stirring device, starting stirring, the stirring speed is 100-150 rpm, the reaction device has two vents, the first vent is passed with argon at 80-100 mL / min, hydrogen at 150-280 mL / min, and vaporized 1.5 mol / L rare earth chloride aqueous solution at 22-31 mL / min, and the second vent is passed with argon at 80-100 mL / min, hydrogen at 150-280 mL / min, and vaporized 1.5 mol / L phosphate aqueous solution at 22-31 mL / min, and the temperature is raised to 1050-1200° C. at 5-15° C. / min, and kept warm for 2 hours to obtain ceramic fiber; the rare earth chloride is lanthanum chloride or cerium chloride, and the phosphate is one of ammonium phosphate, sodium phosphate or phosphoric acid;
[0013] (2) 5-hexenyltriethoxysilane, deionized water, and ethanol were mixed in a mass ratio of 1:4-8:14-24, the pH was adjusted to 4, the ceramic fiber was completely immersed therein, reacted at 70° C. for 1-2 h, taken out, centrifuged and washed 3 times with ethanol at 3000 rpm, and then dried at 60° C. for 24 h to obtain the modified ceramic fiber;
[0014] (3) 80% of sodium dodecylbenzene sulfonate was dissolved in 100 mL of deionized water and stirred at 60° C., sodium (4-vinylphenyl) methanesulfonate was added, and the volume ratio of sodium (4-vinylphenyl) methanesulfonate to deionized water was 0.49-1.0:30-40, and emulsification was performed at 300-500 rpm for 20-25 min. 60% of potassium persulfate was added, and stirring was continued at 75° C. and 300-500 rpm for 10 min to obtain a pre-emulsion; 10 mL of deionized water and the remaining 20% (4-vinylphenyl) methanesulfonate were mixed and the mixture was stirred at 75° C. and 300-500 rpm for 10 min to obtain a pre-emulsion; alkylphenyl) sodium methanesulfonate, the remaining 40% of potassium persulfate, stirred at 300-500rpm for 8min, added 30-40mL of pre-emulsion, heated to 75°C, added 10mL of pre-emulsion, stirred at 300-500rpm for 6h to obtain a microemulsion, added 95% ethanol in a mass fraction of 1 times the volume of the microemulsion, allowed to stand in an ice bath, allowed to stand for stratification, took the lower layer of solid after centrifugation, washed 3 times with 95% ethanol by mass fraction, and dried at 40°C to constant weight to obtain sulfonic acid polystyrene microspheres;
[0015] (4) placing the sulfonated polystyrene microspheres in a reaction device with a stirring device, starting stirring at a speed of 100 to 150 rpm, adding a 1.5 wt% oxidized starch aqueous solution of 1.0 to 1.1 times the micro mass of the sulfonated polystyrene, heating to 90 to 95° C., stirring for 0.5 to 1 h, then adding a modified ceramic fiber of 2 to 5 times the micro mass of the sulfonated polystyrene, stirring for 44 to 66 min, and then freezing at -18° C. for 24 h to obtain a core-shell flame retardant.
[0016] Furthermore, the preparation method of the silica fiber in step (1) is as follows: 1.2-2.0 mL of tetraethyl orthosilicate and 10 mL of anhydrous ethanol are mixed, and the mixture is stirred at 30-60 rpm for 4-6 hours to obtain a silica solution; 0.75-1.1 g of polyvinyl pyrrolidone and 15 g of N,N-dimethylformamide are mixed, and the mixture is stirred at 30-60 rpm for 8-12 hours, and then all of the mixture is added to the silica solution, and stirred at 30-60 rpm for 2-5 hours. Then, the silica precursor fiber with an aspect ratio of 10-20 is electrospun at a voltage of 15-20 kV, a solution flow rate of 0.5-2 mL / h, and a working distance of 15-20 cm from the needle to the collecting plate, and the silica fiber is obtained by constant temperature at 520-600° C. for 3-5 hours.
[0017] Furthermore, in step (3), the mass ratio of sodium dodecylbenzene sulfonate, potassium persulfate and sodium (4-vinylphenyl) methanesulfonate is 5:0.4:90.
[0018] Furthermore, the mass ratio of the core-shell flame retardant, polyethylene resin, lubricant and antioxidant is 10-20:100:1-5:1-5, and the flame retardant layer is extruded by a single screw extruder at an extrusion temperature of 180-188°C.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The present invention adopts a core-shell structured flame retardant as filler and co-extrudes it with polyethylene as a cable sheath material to achieve a highly efficient flame retardant effect of the cable.
[0021] The present invention adopts silica fiber as raw material, and uses rare earth chloride and phosphate as vaporized solution respectively, performs dual-gas phase modification treatment on the silica fiber, generates phosphorus-containing silicon-rare earth ceramic fiber, and uses the fiber as heat-insulating filler in the cable sheath material to isolate heat transfer, thereby interrupting combustion and achieving a flame retardant effect. The presence of rare earth and phosphorus elements can promote carbonization during the combustion process of the cable sheath, and then uses 5-hexenyltriethoxysilane to modify the fiber, thereby enhancing the compatibility of the ceramic fiber with the polyethylene sheath material, thereby improving the dispersibility in the sheath layer, and thereby better exerting the heat-insulating and flame-retardant effect.
[0022] The invention uses sodium (4-vinylphenyl) methanesulfonate as a monomer, polymerizes and prepares sulfonic acid polystyrene microspheres, which are then used as a core layer, and starch is used as an adhesive to adhere modified ceramic fibers on the surface of the microspheres, thereby forming a core-shell flame retardant. The polystyrene has an oxygen isolation effect, and synergistically acts with the heat insulation of the fiber to interrupt combustion and improve the flame retardancy of the cable. The sulfonic acid groups of the microspheres are used as an acid source to decompose and release sulfuric acid substances during combustion. The generated acid combines with the starch carbon source to produce an esterification reaction, which promotes the flame retardant carbonization of the condensed phase, improves the quality and continuity of the carbon layer, and prevents secondary combustion caused by molten droplets. In addition, the existence of the core-shell structure drives the uniform dispersion of the core layer, which is beneficial to optimizing the flame retardancy of the cable. At the same time, the heat insulation effect of the shell layer prevents the polystyrene from being decomposed prematurely, thereby avoiding affecting the quality of the carbon layer. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] (1) 1.2 mL of tetraethyl orthosilicate and 10 mL of anhydrous ethanol were mixed and stirred at 30 rpm for 4 h to obtain a silica solution, 0.75 g of polyvinyl pyrrolidone and 15 g of N,N-dimethylformamide were mixed and stirred at 30 rpm for 8 h, all of which were added to the silica solution and stirred at 30 rpm for 2 to 5 h, and then electrospun at a voltage of 15 kV, a solution flow rate of 0.5 mL / h, and a working distance of 15 cm from the needle to the collecting plate to obtain a silica precursor fiber with an aspect ratio of 10, and kept at 520° C. for 3 h to obtain silica fibers;
[0026] (2) placing the silica fiber in a reaction device with a stirring device, starting stirring, the stirring speed is 100 rpm, the reaction device has two vents, the first vent is introduced with argon at 80 mL / min, hydrogen at 150 mL / min, and vaporized 1.5 mol / L lanthanum chloride aqueous solution at 22 mL / min, and the second vent is introduced with argon at 80 mL / min, hydrogen at 150 mL / min, and vaporized 1.5 mol / L ammonium phosphate aqueous solution at 22 mL / min, and the temperature is raised to 1050° C. at 5° C. / min, and kept warm for 2 h to obtain ceramic fiber;
[0027] (3) 5-hexenyltriethoxysilane, deionized water, and ethanol were mixed in a mass ratio of 1:4:14, the pH was adjusted to 4, the ceramic fiber was completely immersed therein, reacted at 70° C. for 1 h, taken out, centrifuged and washed 3 times with ethanol at 3000 rpm, and then dried at 60° C. for 24 h to obtain the modified ceramic fiber;
[0028] (4) 80% of sodium dodecylbenzene sulfonate was dissolved in 100 mL of deionized water. The mixture was stirred at 60° C., sodium (4-vinylphenyl) methanesulfonate was added, and the volume ratio of sodium (4-vinylphenyl) methanesulfonate to deionized water was 0.49:30. The mixture was emulsified at 300 rpm for 20 min. 60% of potassium persulfate was added, and the mixture was stirred at 75° C. and 300 rpm for another 10 min to obtain a pre-emulsified solution. 10 mL of deionized water and the remaining 20% of sodium (4-vinylphenyl) methanesulfonate and the remaining 40% of potassium persulfate were mixed at 300 rpm for 300 min. After stirring for 8 min, 30 mL of pre-emulsion was added, the temperature was raised to 75 ° C, 10 mL of pre-emulsion was added, and the mixture was stirred at 300 rpm for 6 h to obtain a microemulsion, 95% ethanol was added in an amount of 1 times the volume of the microemulsion, and the mixture was allowed to stand in an ice bath for stratification. The solid after centrifugation of the lower layer was taken out, washed three times with 95% ethanol by mass, and dried at 40 ° C to constant weight to obtain sulfonic acid polystyrene microspheres; the mass ratio of sodium dodecylbenzene sulfonate, potassium persulfate, and sodium (4-vinylphenyl) methanesulfonate was 5:0.4:90;
[0029] (5) placing the sulfonic acid polystyrene microspheres in a reaction device with a stirring device, starting stirring at a stirring speed of 100 rpm, adding a 1.5 wt% oxidized starch aqueous solution of 1 times the micro mass of the sulfonic acid polystyrene, heating to 90° C., stirring for 0.5 h, then adding modified ceramic fibers of 2 times the micro mass of the sulfonic acid polystyrene, stirring for 44 min, and then freezing at -18° C. for 24 h to obtain a core-shell flame retardant;
[0030] (6) Linear low-density polyethylene, high-density polyethylene, and ethylene-vinyl acetate copolymer are mixed in a weight ratio of 40:10:20 to obtain polyethylene resin; a core-shell flame retardant, polyethylene resin, polyethylene wax, and dilauryl thiodipropionate are extruded into a copper braided shielded cable core at a mass ratio of 10:100:1:1 at 180-188° C. to obtain a cable.
[0031] Example 2
[0032] (1) 1.8 mL of tetraethyl orthosilicate and 10 mL of anhydrous ethanol were mixed and stirred at 40 rpm for 5 h to obtain a silica solution, 0.92 g of polyvinyl pyrrolidone and 15 g of N,N-dimethylformamide were mixed and stirred at 40 rpm for 10 h, all of which were added to the silica solution and stirred at 40 rpm for 3.5 h, and then electrospun at a voltage of 18 kV, a solution flow rate of 1.4 mL / h, and a working distance of 18 cm from the needle to the collecting plate to obtain a silica precursor fiber with an aspect ratio of 15, and the silica fiber was obtained by constant temperature at 570° C. for 4 h;
[0033] (2) placing the silica fiber in a reaction device with a stirring device, starting stirring, the stirring speed is 120 rpm, the reaction device has two vents, the first vent is introduced with argon at 90 mL / min, hydrogen at 210 mL / min, and vaporized 1.5 mol / L cerium chloride aqueous solution at 26 mL / min, and the second vent is introduced with argon at 90 mL / min, hydrogen at 210 mL / min, and vaporized 1.5 mol / L sodium phosphate aqueous solution at 26 mL / min, and the temperature is raised to 1100° C. at 10° C. / min, and kept warm for 2 h to obtain ceramic fiber;
[0034] (3) 5-hexenyltriethoxysilane, deionized water, and ethanol were mixed in a mass ratio of 1:6:20, the pH was adjusted to 4, the ceramic fiber was completely immersed therein, reacted at 70° C. for 1.5 h, taken out, centrifuged and washed three times with ethanol at 3000 rpm, and then dried at 60° C. for 24 h to obtain the modified ceramic fiber;
[0035] (4) 80% of sodium dodecylbenzene sulfonate was dissolved in 100 mL of deionized water. The mixture was stirred at 60° C., sodium (4-vinylphenyl) methanesulfonate was added, and the volume ratio of sodium (4-vinylphenyl) methanesulfonate to deionized water was 0.72:35. The mixture was emulsified at 400 rpm for 22 min. 60% of potassium persulfate was added, and the mixture was stirred at 75° C. and 400 rpm for another 10 min to obtain a pre-emulsified solution. 10 mL of deionized water and the remaining 20% of sodium (4-vinylphenyl) methanesulfonate and the remaining 40% of potassium persulfate were mixed at 400 rpm for 22 min. After stirring for 8 minutes, 35 mL of pre-emulsion was added, the temperature was raised to 75 ° C, 10 mL of pre-emulsion was added, and the mixture was stirred at 400 rpm for 6 hours to obtain a microemulsion, 95% ethanol was added in an amount of 1 times the volume of the microemulsion, and the mixture was allowed to stand in an ice bath for stratification. The solid after centrifugation of the lower layer was taken and washed three times with 95% ethanol by mass fraction, and dried at 40 ° C to constant weight to obtain sulfonic acid polystyrene microspheres; the mass ratio of sodium dodecylbenzene sulfonate, potassium persulfate, and sodium (4-vinylphenyl) methanesulfonate was 5:0.4:90;
[0036] (5) placing the sulfonic acid polystyrene microspheres in a reaction device with a stirring device, starting stirring at a stirring speed of 120 rpm, adding a 1.5 wt% oxidized starch aqueous solution of 1.05 times the micro mass of the sulfonic acid polystyrene, heating to 92° C., stirring for 0.8 h, then adding a modified ceramic fiber of 3.5 times the micro mass of the sulfonic acid polystyrene, stirring for 53 min, and then freezing at -18° C. for 24 h to obtain a core-shell flame retardant;
[0037] (6) Linear low-density polyethylene, high-density polyethylene, and ethylene-vinyl acetate copolymer are mixed in a weight ratio of 45:15:28 to obtain polyethylene resin; a core-shell flame retardant, polyethylene resin, zinc stearate, and antioxidant 1010 are extruded into a copper braided shielded cable core at a mass ratio of 15:100:3:3 at 180-188° C. to obtain a cable.
[0038] Example 3
[0039] (1) 2.0 mL of tetraethyl orthosilicate and 10 mL of anhydrous ethanol were mixed and stirred at 60 rpm for 6 h to obtain a silica solution, 1.1 g of polyvinyl pyrrolidone and 15 g of N,N-dimethylformamide were mixed and stirred at 60 rpm for 12 h, all of which were added to the silica solution and stirred at 60 rpm for 5 h, and then electrospun at a voltage of 20 kV, a solution flow rate of 2 mL / h, and a working distance of 20 cm from the needle to the collecting plate to obtain a silica precursor fiber with an aspect ratio of 20, and then kept at 600° C. for 5 h to obtain silica fibers;
[0040] (2) placing the silica fiber in a reaction device with a stirring device, starting stirring, the stirring speed is 150 rpm, the reaction device has two vents, the first vent is introduced with argon at 100 mL / min, hydrogen at 280 mL / min, and vaporized 1.5 mol / L lanthanum chloride aqueous solution at 31 mL / min, and the second vent is introduced with argon at 100 mL / min, hydrogen at 280 mL / min, and vaporized 1.5 mol / L phosphoric acid aqueous solution at 31 mL / min, and the temperature is raised to 1200° C. at 15° C. / min, and kept warm for 2 h to obtain ceramic fiber;
[0041] (3) 5-hexenyltriethoxysilane, deionized water, and ethanol were mixed in a mass ratio of 1:8:24, the pH was adjusted to 4, the ceramic fiber was completely immersed therein, reacted at 70° C. for 2 h, taken out, centrifuged and washed 3 times with ethanol at 3000 rpm, and then dried at 60° C. for 24 h to obtain the modified ceramic fiber;
[0042] (4) 80% of sodium dodecylbenzene sulfonate was dissolved in 100 mL of deionized water. The mixture was stirred at 60° C., sodium (4-vinylphenyl) methanesulfonate was added, and the volume ratio of sodium (4-vinylphenyl) methanesulfonate to deionized water was 1.0:40. The mixture was emulsified at 500 rpm for 25 min. 60% of potassium persulfate was added, and the mixture was stirred at 75° C. and 500 rpm for another 10 min to obtain a pre-emulsified solution. 10 mL of deionized water and the remaining 20% of sodium (4-vinylphenyl) methanesulfonate and the remaining 40% of potassium persulfate were mixed at 500 rpm. m after stirring for 8 minutes, adding 40 mL of pre-emulsion, heating to 75 ° C, adding 10 mL of pre-emulsion, stirring at 500 rpm for 6 hours to obtain a microemulsion, adding 95% ethanol with a mass fraction of 1 times the volume of the microemulsion, standing in an ice bath, standing for stratification, taking the solid after centrifugation, washing it three times with 95% ethanol by mass fraction, and drying it at 40 ° C to constant weight to obtain sulfonic acid polystyrene microspheres; the mass ratio of sodium dodecylbenzene sulfonate, potassium persulfate, and sodium (4-vinylphenyl) methanesulfonate is 5:0.4:90;
[0043] (5) placing the sulfonic acid polystyrene microspheres in a reaction device with a stirring device, starting stirring at a stirring speed of 150 rpm, adding a 1.5 wt% oxidized starch aqueous solution of 1.1 times the micro mass of the sulfonic acid polystyrene, heating to 95° C., stirring for 1 hour, then adding a modified ceramic fiber of 5 times the micro mass of the sulfonic acid polystyrene, stirring for 66 minutes, and then freezing at -18° C. for 24 hours to obtain a core-shell flame retardant;
[0044] (6) Linear low-density polyethylene, high-density polyethylene, and ethylene-vinyl acetate copolymer are mixed in a weight ratio of 50:20:35 to obtain polyethylene resin; a core-shell flame retardant, polyethylene resin, polyethylene wax, and antioxidant 1010 are extruded into a copper braided shielded cable core at a mass ratio of 20:100:5:5 at 180-188° C. to obtain a cable.
[0045] Comparative Example 1
[0046] (1) 1.8 mL of tetraethyl orthosilicate and 10 mL of anhydrous ethanol were mixed and stirred at 40 rpm for 5 h to obtain a silica solution, 0.92 g of polyvinyl pyrrolidone and 15 g of N,N-dimethylformamide were mixed and stirred at 40 rpm for 10 h, all of which were added to the silica solution and stirred at 40 rpm for 3.5 h, and then electrospun at a voltage of 18 kV, a solution flow rate of 1.4 mL / h, and a working distance of 18 cm from the needle to the collecting plate to obtain a silica precursor fiber with an aspect ratio of 15, and the silica fiber was obtained by constant temperature at 570° C. for 4 h;
[0047] (2) 5-hexenyltriethoxysilane, deionized water and ethanol were mixed in a mass ratio of 1:6:20, the pH was adjusted to 4, the silica fiber was completely immersed therein, reacted at 70°C for 1.5 hours, taken out, centrifuged and washed three times with ethanol at 3000 rpm, and then dried at 60°C for 24 hours to obtain modified silica fiber;
[0048] (3) 80% of sodium dodecylbenzene sulfonate was dissolved in 100 mL of deionized water. The mixture was stirred at 60° C., sodium (4-vinylphenyl) methanesulfonate was added, and the volume ratio of sodium (4-vinylphenyl) methanesulfonate to deionized water was 0.72:35. The mixture was emulsified at 400 rpm for 22 min. 60% of potassium persulfate was added, and the mixture was stirred at 75° C. and 400 rpm for another 10 min to obtain a pre-emulsified solution. 10 mL of deionized water and the remaining 20% of sodium (4-vinylphenyl) methanesulfonate and the remaining 40% of potassium persulfate were mixed at 400 rpm for 22 min. After stirring for 8 minutes, 35 mL of pre-emulsion was added, the temperature was raised to 75 ° C, 10 mL of pre-emulsion was added, and the mixture was stirred at 400 rpm for 6 hours to obtain a microemulsion, 95% ethanol was added in an amount of 1 times the volume of the microemulsion, and the mixture was allowed to stand in an ice bath for stratification. The solid after centrifugation of the lower layer was taken and washed three times with 95% ethanol by mass fraction, and dried at 40 ° C to constant weight to obtain sulfonic acid polystyrene microspheres; the mass ratio of sodium dodecylbenzene sulfonate, potassium persulfate, and sodium (4-vinylphenyl) methanesulfonate was 5:0.4:90;
[0049] (4) placing the sulfonic acid polystyrene microspheres in a reaction device with a stirring device, starting stirring at a stirring speed of 120 rpm, adding a 1.5 wt% oxidized starch aqueous solution of 1.05 times the micro mass of the sulfonic acid polystyrene, heating to 92° C., stirring for 0.8 h, then adding modified silica fiber of 3.5 times the micro mass of the sulfonic acid polystyrene, stirring for 53 min, and then freezing at -18° C. for 24 h to obtain a core-shell flame retardant;
[0050] (5) Linear low-density polyethylene, high-density polyethylene, and ethylene-vinyl acetate copolymer are mixed in a weight ratio of 45:15:28 to obtain polyethylene resin; a core-shell flame retardant, polyethylene resin, zinc stearate, and antioxidant 1010 are extruded into a copper braided shielded cable core at a mass ratio of 15:100:3:3 at 180-188° C. to obtain a cable.
[0051] Comparative Example 2
[0052] The difference between Comparative Example 2 and Example 2 is that there is no step (3), and step (5) is changed to: placing the sulfonated polystyrene microspheres in a reaction device with a stirring device, starting stirring, the stirring speed is 120 rpm, adding 1.5 wt% oxidized starch aqueous solution with a micro mass of 1.05 times the micro mass of the sulfonated polystyrene, heating to 92°C, stirring for 0.8h, and then adding ceramic fiber with a micro mass of 3.5 times the micro mass of the sulfonated polystyrene, stirring for 53min, and then freezing at -18°C for 24h to obtain a core-shell flame retardant; the remaining steps are the same as those in Example 2.
[0053] Comparative Example 3
[0054] The difference between Comparative Example 3 and Example 2 is that there is no step (4), and step (5) is changed to: placing polystyrene microspheres in a reaction device with a stirring device, starting stirring, the stirring speed is 120 rpm, adding 1.5 wt% oxidized starch aqueous solution with a micro mass of 1.05 times the micro mass of polystyrene, heating to 92°C, stirring for 0.8h, then adding modified ceramic fiber with a micro mass of 3.5 times the micro mass of polystyrene, stirring for 53min, and then freezing at -18°C for 24h to obtain a core-shell flame retardant; the remaining steps are the same as Example 2.
[0055] Comparative Example 4
[0056] The difference between Comparative Example 4 and Example 2 is that there is no step (5), and step (6) is changed to: linear low-density polyethylene, high-density polyethylene, and ethylene-vinyl acetate copolymer are mixed in a weight ratio of 45:15:28 to obtain polyethylene resin; sulfonate polystyrene microspheres, modified ceramic fibers, polyethylene resin, zinc stearate, and antioxidant 1010 are extruded into a copper braided shielded cable core in a mass ratio of 15:15:100:3:3 at 180-188°C to obtain a flame retardant layer to obtain a cable.
[0057] Effect example
[0058] Table 1 below shows the performance analysis results of the cables using Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.
[0059] Table 1
[0060]
[0061] The present invention uses sulfonic acid polystyrene microspheres as the core layer, uses starch as an adhesive, and adheres modified ceramic fibers to the surface of the microspheres, thereby forming a core-shell flame retardant. Polystyrene has an oxygen isolation effect, and synergistically acts with the heat insulation of the fiber to interrupt combustion and improve the flame retardancy of the cable. The sulfonic acid groups of the microspheres act as an acid source and decompose to release sulfuric acid substances during combustion. The generated acid combines with the starch carbon source to produce an esterification reaction, which promotes the flame retardant carbonization of the condensed phase, improves the quality and continuity of the carbon layer, and prevents secondary combustion caused by molten droplets. In addition, the presence of the core-shell structure drives the uniform dispersion of the core layer, which is beneficial to optimizing the flame retardancy of the cable. At the same time, the heat insulation effect of the shell layer prevents the polystyrene from decomposing prematurely and avoids affecting the quality of the carbon layer.
[0062] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A halogen-free flame-retardant cable, comprising a copper conductor, a polyethylene insulation layer, a copper braided shielding layer, and a flame-retardant layer, characterized in that: The flame retardant layer is composed of core-shell flame retardant, polyethylene resin, lubricant and antioxidant.
2. A halogen-free flame-retardant cable according to claim 1, characterized in that: The polyethylene resin is a mixture of linear low-density polyethylene, high-density polyethylene and ethylene-vinyl acetate copolymer in a weight ratio of 40-50:10-20:20-35.
3. A halogen-free flame-retardant cable according to claim 2, characterized in that: The density of the linear low-density polyethylene is 0.920 g / cm 3 , the melt index is 2.0g / 10min.
4. A halogen-free flame-retardant cable according to claim 2, characterized in that: The density of the high-density polyethylene is 0.953 g / cm 3 , the melt index is 0.4g / 10min.
5. The halogen-free flame-retardant cable according to claim 1, characterized in that: The lubricant is polyethylene wax or zinc stearate.
6. The halogen-free flame-retardant cable according to claim 1, characterized in that: The antioxidant is dilauryl thiodipropionate or antioxidant 1010.
7. The halogen-free flame-retardant cable according to claim 1, characterized in that: The preparation method of the core-shell flame retardant is: (1) placing silica fiber in a reaction device with a stirring device, starting stirring, the stirring speed is 100-150 rpm, the reaction device has two vents, the first vent is passed with argon at 80-100 mL / min, hydrogen at 150-280 mL / min, and vaporized 1.5 mol / L rare earth chloride aqueous solution at 22-31 mL / min, and the second vent is passed with argon at 80-100 mL / min, hydrogen at 150-280 mL / min, and vaporized 1.5 mol / L phosphate aqueous solution at 22-31 mL / min, and the temperature is raised to 1050-1200° C. at 5-15° C. / min, and kept warm for 2 hours to obtain ceramic fiber; the rare earth chloride is lanthanum chloride or cerium chloride, and the phosphate is one of ammonium phosphate, sodium phosphate or phosphoric acid; (2) 5-hexenyltriethoxysilane, deionized water, and ethanol were mixed in a mass ratio of 1:4-8:14-24, the pH was adjusted to 4, the ceramic fiber was completely immersed therein, reacted at 70° C. for 1-2 h, taken out, centrifuged and washed 3 times with ethanol at 3000 rpm, and then dried at 60° C. for 24 h to obtain the modified ceramic fiber; (3) 80% of sodium dodecylbenzene sulfonate was dissolved in 100 mL of deionized water and stirred at 60° C., sodium (4-vinylphenyl) methanesulfonate was added, and the volume ratio of sodium (4-vinylphenyl) methanesulfonate to deionized water was 0.49-1.0:30-40, and emulsification was performed at 300-500 rpm for 20-25 min. 60% of potassium persulfate was added, and stirring was continued at 75° C. and 300-500 rpm for 10 min to obtain a pre-emulsion; 10 mL of deionized water and the remaining 20% (4-vinylphenyl) methanesulfonate were mixed and the mixture was stirred at 75° C. and 300-500 rpm for 10 min to obtain a pre-emulsion; alkylphenyl) sodium methanesulfonate, the remaining 40% of potassium persulfate, stirred at 300-500rpm for 8min, added 30-40mL of pre-emulsion, heated to 75°C, added 10mL of pre-emulsion, stirred at 300-500rpm for 6h to obtain a microemulsion, added 95% ethanol in a mass fraction of 1 times the volume of the microemulsion, allowed to stand in an ice bath, allowed to stand for stratification, took the lower layer of solid after centrifugation, washed 3 times with 95% ethanol by mass fraction, and dried at 40°C to constant weight to obtain sulfonic acid polystyrene microspheres; (4) placing the sulfonated polystyrene microspheres in a reaction device with a stirring device, starting stirring at a speed of 100 to 150 rpm, adding a 1.5 wt% oxidized starch aqueous solution of 1.0 to 1.1 times the micro mass of the sulfonated polystyrene, heating to 90 to 95° C., stirring for 0.5 to 1 h, then adding a modified ceramic fiber of 2 to 5 times the micro mass of the sulfonated polystyrene, stirring for 44 to 66 min, and then freezing at -18° C. for 24 h to obtain a core-shell flame retardant.
8. The halogen-free flame-retardant cable according to claim 7, characterized in that: The preparation method of the silica fiber in step (1) is as follows: 1.2-2.0 mL of tetraethyl orthosilicate and 10 mL of anhydrous ethanol are mixed, and the mixture is stirred at 30-60 rpm for 4-6 h to obtain a silica solution; 0.75-1.1 g of polyvinyl pyrrolidone and 15 g of N,N-dimethylformamide are mixed, and the mixture is stirred at 30-60 rpm for 8-12 h, and then all of the mixture is added to the silica solution, and the mixture is stirred at 30-60 rpm for 2-5 h. Then, the silica precursor fiber with an aspect ratio of 10-20 is electrospun at a voltage of 15-20 kV, a solution flow rate of 0.5-2 mL / h, and a working distance of 15-20 cm from the needle to the collecting plate, and the silica fiber is obtained by constant temperature at 520-600° C. for 3-5 h.
9. The halogen-free flame-retardant cable according to claim 7, characterized in that: The mass ratio of sodium dodecylbenzene sulfonate, potassium persulfate and sodium (4-vinylphenyl) methanesulfonate in step (3) is 5:0.4:
90.
10. The halogen-free flame-retardant cable according to claim 1, characterized in that: The mass ratio of the core-shell flame retardant, polyethylene resin, lubricant and antioxidant is 10-20:100:1-5:1-5. The flame retardant layer is extruded by a single screw extruder at a temperature of 180-188°C.
Citation Information
Patent Citations
Preparation method for preparing super-hydrophobic cross-linked silica fiber foams
CN106567248A
Enzymatic degradation of plastic polyalkene polymers by KATG enzyme
WO2021205160A1